(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
The electron beam machine (EBM) irradiators based on plasma cathode that emit pulse electron beam for radiation vulcanized natural rubber latex (RVNRL) have been developed in Tomsk, Russia. Meanwhile, a prototype of an ultraviolet light-emitting diode (UV-LED) irradiator for RVNRL has been developed by the Research Technology Center for Accelerator and the ATK Polytechnic in Yogyakarta, Indonesia. This research aims to compare the irradiator prototype technology for RVNRL. The RVNRL technology comparison method is carried out by assessing the specifications and performance of the equipment, costs (investment, operational, maintenance), hazard, and operability. The results of the comparison of irradiator technology for RVNRL show that the UV-LED irradiators are superior to the UV-mercury irradiators and the plasma cathode-based EBM irradiators which gives a total value of 476, 412, and 248, respectively. Thus, it can be concluded that the UV-LED irradiators technology for RVNRL is simpler, more practical, economical, and environmentally friendly compared to the UV-mercury irradiators and the plasma cathode-based EBM irradiators.